Tethered Lipid Membranes as a Nanoscale Arrangement towards Non-Invasive Analysis of Acute Pancreatitis - Rima Budvytyte; Akvile Milasiute; Dalius Vitkus; Kestutis Strupas; Aiste Gulla; Ieva Sakinyte; Julija Razumiene (Biomedicines, 2021)
Extracellular heat shock proteins (HSPs) mediate immunological functions and are involved in pathologies such as infection, stress, and cancer. Here, we demonstrated the dependence of an amount of HSP70 and HSP90 in serum vs. severity of acute pancreatitis (AP) on a cohort of 49 patients. Tethered bilayer lipid membranes (tBLMs) have been developed to investigate HSPs’ interactions with tBLMs that can be probed by electrochemical impedance spectroscopy (EIS). The results revealed that HSP70 and HSP90 interact via different mechanisms. HSP70 shows the damage of the membrane, while HSP90 increases the insulation properties of tBLM. These findings provide evidence that EIS offers a novel approach for the study of the changes in membrane integrity induced by HSPs proteins. Herein, we present an alternative electrochemical technique, without any immunoprobes, that allows for the monitoring of HSPs on nanoscaled tBLM arrangement in biologics samples such us human urine. This study demonstrates the great potential of tBLM to be used as a membrane based biosensor for novel, simple, and non-invasive label-free analytical system for the prediction of AP severity.